2003
DOI: 10.1080/1350485032000100305
|View full text |Cite
|
Sign up to set email alerts
|

Can confidence indicators be useful to predict short term real GDP growth?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 2 publications
4
21
1
1
Order By: Relevance
“…Data lags and data revisions lengthen the measuring processes, while the confidence indicators track the major cyclical movements of industrial production. If Santero and Westerlund identified a limit in the use of confidence indicators for the performance of short-run forecasts, due to lack of a sequential behaviour consistent with the movements in the production activity, Mourougane and Roma considered that these can be useful in forecasting the growth rates of GDP [48]. Using a Dynamic Factor Model (DFM), Hansson and Jansson showed that, for Sweden, the data from the business tendency surveys are useful for forecasting the short-run GDP evolution [49].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Data lags and data revisions lengthen the measuring processes, while the confidence indicators track the major cyclical movements of industrial production. If Santero and Westerlund identified a limit in the use of confidence indicators for the performance of short-run forecasts, due to lack of a sequential behaviour consistent with the movements in the production activity, Mourougane and Roma considered that these can be useful in forecasting the growth rates of GDP [48]. Using a Dynamic Factor Model (DFM), Hansson and Jansson showed that, for Sweden, the data from the business tendency surveys are useful for forecasting the short-run GDP evolution [49].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…The bridging equation technique was first developed extensively for the US GNP by Klein and Sojo (1989), with further examples and derivations seen in (amongst others) Baffigi et al (2002Baffigi et al ( , 2004, Grasmann and Keereman (2001), Ingenito and Trehan (1996), Mourougane and Roma (2002), Parigi and Schlitzer (1995) and Rünstler et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…Studies in Europe have found a consistent connection between consumer confidence measures and economic activity for various countries. These include those of Acemoglu and Scott (1994) for the United Kingdom, Berg and Bergstrom (1996) for Sweden, Hüfner and Schröder (2002) for Germany, and Mourougane and Roma (2002) for five European countries.…”
Section: Previous Research On Confidencementioning
confidence: 99%
“…These include the work of Carroll et al (1994), who find that lagged values of sentiment can explain about 14% of the variation in the growth of real consumption in the United States over a 40‐year period beginning in 1954, with at least some part of the impact probably not being merely a reflection of income. Souleles (2002) finds that sentiment can be useful in forecasting consumption and that cross‐sectional variation in confidence can be informative. In particular, he finds that questions asking specifically about the household condition do better than those asking about the general economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation